COMPLEX CORRECTION OF VASCULAR HEMOSTASIS IN PATIENTS WITH ARTERIAL HYPERTENSION, METABOLIC SYNDROME, AND RECENT OCULAR VESSEL OCCLUSION - I. N. Medvedev; O. A. Danilenko (Российский кардиологический журнал)
The study was aimed at the evaluation of complex therapy (diltiazem, pioglitazone, and non-pharmaceutical measures) in the correction of anticoagulant, fibrinolytic, and anti-aggregant vascular wall activity among patients with arterial hypertension, metabolic syndrome, and recent ocular vessel occlusion. It was demonstrated that after 4 months of the above-mentioned complex therapy, the anticoagulant, fibrinolytic, and anti-aggregant vascular wall activity was improved, but not normalised. At the same time, the investigated parameters significantly deteriorated if the non-pharmaceutical therapy compliance was low.